2015
DOI: 10.5539/elt.v8n11p231
|View full text |Cite
|
Sign up to set email alerts
|

The Effective of Computer-Assisted Instruction Based on Top-Level Structure Method in English Reading and Writing Abilities of Thai EFL Students

Abstract: This research aims to study the development of ninth grade students' reading and writing abilities and interests in learning English taught through computer-assisted instruction (CAI) based on the top-level structure (TLS) method. An experimental group time series design was used, and the data was analyzed by multivariate analysis of variance (MANOVA) with repeated measures as well as basic statistical and line graphs. The results demonstrate that the experimental group attained significantly higher developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…According to Aloraini (2012), she concluded that finding the impact of using multimedia on female students ' academic achievement and the results showed that using multimedia in education is an effective way to achieve better learning. Moreover, the results of the study of Jinajai & Rattanavich (2015) the field of English language and creative writing, using the TLS method-based CAI are useful. Students in the ninth grade have significantly increased English performance, particularly in reading and writing skills, may explain the results of this study.…”
Section: Advantages In Utilizing Computer-based Technology In Science Instructionmentioning
confidence: 99%
“…According to Aloraini (2012), she concluded that finding the impact of using multimedia on female students ' academic achievement and the results showed that using multimedia in education is an effective way to achieve better learning. Moreover, the results of the study of Jinajai & Rattanavich (2015) the field of English language and creative writing, using the TLS method-based CAI are useful. Students in the ninth grade have significantly increased English performance, particularly in reading and writing skills, may explain the results of this study.…”
Section: Advantages In Utilizing Computer-based Technology In Science Instructionmentioning
confidence: 99%
“…As the economic globalization deepens, the communication between China and other countries is more and more frequent, and the most frequently used language is English. English teaching includes five aspects, listening, speaking, reading, writing and translation, among which writing teaching is the most important and difficult part [1]. English writing ability can be improved through a large number of writing exercises and comments of teachers.…”
Section: Introductionmentioning
confidence: 99%